Fuzzy Analytic Hierarchy Process (FAHP) for Better Selection during Implementation of Design for Remanufacturing in Economy Indicator / Ahamad Zaki Mohamed Noor... [et al.] - Mohamed Noor, Ahamad Zaki; Md Fauadi, Muhammad Hafidz Fazli; Jafar, Fairul Azni (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Remanufacturing is a process of repair, reuse or replace parts of a product to extend its life with minimal waste of money and energy during the process. Design of Remanufacturing (DFReM) consists of three indicators namely social, environmental and economic. In this paper, the economic indicator will be improved by implementing Fuzzy Analytic Hierarchy Process (FAHP) during cost selection. More often than not, industries ignore this practice due to time restriction. However, the industries do not realise that with more time spent on classifying costs, the more the revenue a company may reap through proper usage of DFReM. Data from three manufacturing industries that produce steel-reinforced plastic cable tight were acquired in the present investigation. The objective of this study is to identify the best cost selection prior to its substitution in the DFReM economy indicator equation. FAHP is employed to select the minimum cost and distance out of all three options. It was demonstrated from the study that FAHP could determine the optimum selection that yields the highest profit.